2006
DOI: 10.1080/17421770601009841
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Durbin Model and the Common Factor Tests

Abstract: The spatial Durbin model occupies an interesting position in the field of spatial econometrics. It is the reduced form of a model with cross-sectional dependence in the errors and it may be used as the nesting equation in a more general approach of model selection. Specifically, in this equation we obtain the common factor tests (of which the likelihood ratio is the best known) whose objective is to discriminate between substantive and residual dependence in an apparently misspecified equation. Our paper tries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…These problems may be due to various spatially related misspecifications common to most applied hedonic house price analyses and are an argument in favour of the SDM. To study further this issue of specification, a common factor constraints hypothesis test has been performed (Bivand, 1984;Mur and Angulo, 2006 This is a test of the null hypothesis that the coefficients of the OLS model and the corresponding spatial error model are equal. The null hypothesis has to be rejected and is an additional support of the SDM.…”
Section: Estimation Results and Spatial Spillover Effects From The Bmmentioning
confidence: 99%
“…These problems may be due to various spatially related misspecifications common to most applied hedonic house price analyses and are an argument in favour of the SDM. To study further this issue of specification, a common factor constraints hypothesis test has been performed (Bivand, 1984;Mur and Angulo, 2006 This is a test of the null hypothesis that the coefficients of the OLS model and the corresponding spatial error model are equal. The null hypothesis has to be rejected and is an additional support of the SDM.…”
Section: Estimation Results and Spatial Spillover Effects From The Bmmentioning
confidence: 99%
“…In the next section, we will present a list of the alternative model formulations to be estimated. Osland and Thorsen (, ) have tested Models 1 and 2 in the list of alternatives for spatial effects, by using robust Lagrange multiplier tests (Osland, ) and the common factor hypothesis test (Mur and Angulo, ). The results from these tests showed that there are still significant spatial effects in the residuals.…”
Section: The Modeling Frameworkmentioning
confidence: 99%
“…Second, we use spatial Durbin models (SDMs) to examine spatial lags on our dependent and explanatory variables (Mur and Angulo 2006). The SDMs capture feedback influences between variables-that is, the impacts passing through neighbouring subdistricts and back to a subdistrict itself (Elhorst 2010).…”
Section: Model Specifications With Spatial Dependencementioning
confidence: 99%